Foreign bodies in the torax - Ćerimagić Zenaida; Guska Safet; Kadić Kenan; Banjanović Bedrudin (Vojnosanitetski Pregled)
Background. Metallic foreign bodies in the lung could be recognized using radiography. Non-metallic foreign bodies make difficulties because they are not as dense as metals. The aim of this report was to present the case of nonmetallic foreign bodies in the lung. Case report. A soldier of the Federation Army of Bosnia and Hertzegovina, injured in the explosion in 1998 was presented. The soldier was subjected to thoracic drainage and surgery tretment of the wound. After one year, the pulmologist treated him with tuberculostatics because of hemoptysis and pulmonary infiltration shown by a radiogram. This therapy had no effects, and the pulmologist presented this case to the thoracic surgeon who made thoracotomy removing a piece of wood (13 × 2 × 0.7 cm), 20 different-size pieces of wood, and a piece of textile from the lung. Conclusion. Patients with penetrating explosive lung injuries without metallic foreign bodies shown by a radiogram, with complications as hemoptisis, lung abscess, bronchiectasis, obstruction of the bronchus, chronic pneumonia should be subjected to thoracotomy for removing suspected foreign bodies without resecting the lung.